A CASE STUDY ON GRIN AND GLUCOSE: THE TWO-WAY STREET OF DIABETES AND ORAL HEALTH. - Aushili M; Shankar, Anand (Student’s Journal of Health Research Africa, 2024)
Background The bidirectional association between diabetes and oral health affects the management of both, as high blood sugar promotes oral bacteria growth and gum disease, while periodontal issues can worsen diabetes control, emphasizing the need for integrated care. The study aimed to explore the mutual influence of diabetes and oral health on each other, particularly examining how gingival health and glucose levels impact the progression and severity of both conditions. Methods This multicenter study enrolled 120 type 2 diabetes mellitus patients, categorized by glycemic control status based on their HbA1c levels. Employing personal interviews with structured questionnaires, the study investigated demographic characteristics, periodontal treatment experience, self-care behaviors, oral health knowledge, attitude towards periodontal health, and oral health-related quality of life (OHQoL). Logistic regression models analyzed the relation between glycemic control status and various periodontal care behaviors. Results The study revealed a notable link between poor glycemic control and periodontal disease (OR = 2.5, p < 0.05), and showed that regular dental visits improve glycemic control (OR = 0.4, p < 0.05). Participants had a moderate understanding of oral health and positive attitudes toward it. Good glycemic control was also associated with better OHQoL scores (95% CI [1.5, 4.5], p < 0.001), yet the quality of periodontal care did not significantly alter OHQoL outcomes, indicating effective periodontal treatment does not negatively impact life quality. Conclusion The study underscores the bidirectional association between glycemic control and periodontal health, emphasizing the importance of integrated care approaches that incorporate both dental and diabetes management strategies. Recommendations Healthcare providers should foster closer collaborations between dental and health professionals to ensure comprehensive care for patients with T2DM. Further research should explore the effectiveness of integrated care models in improving both glycemic control and oral health outcomes.